Analisa Hubungan antara Harga Jual dan Kondisi Stock Produk Makanan Basah Kucing Menggunakan Pendekatan Regresi di Cat Care Petshop - Vibowo, Heryudianto; Sulistiwati, Erni; Suriaatmaja Suwanda, Bayu; Marithasari, Harries (Jurnal Sains Indonesia, 2023)
The Petshop business has been increasing recently. This is related to the economic capacity of the community and changes in several segments of society who are starting to buy food for their beloved pets, cats and dogs. Determining the selling price is a very important thing for Petshop business people to pay attention to in order to increase purchasing power and of course as one of the business people's strategies so that people want to buy animal needs at the Petshop. Apart from that, stock management must also be carried out well by the perpetrators so that there is no accumulation. Selling prices that are too high will cause stock buildup due to poor turnover of goods. This is proven by the influence of selling prices on stock conditions at Cat Care Petshop with a determination value of 82.6%. So Cat Care Petshop must regulate the selling price of feed so that stock availability can be controlled and does not pile up.